Checkpoint, temple, church and mosque : a collaborative ethnography of war and peace - Spencer, Jonathan, 1954-; Goodhand, Jonathan; Hasbullah, S. H.; Klem, Bart; Korf, Benedikt; Silva, Kalinga Tudor, 1949- (Anthropology, culture, and society., 2015)
Checkpoint, temple, church and mosque is based on fieldwork in Sri Lanka's most religiously diverse and politically troubled region in the closing years of the civil war. It provides a series of new and provocative arguments about the promise of a religiously based civil society, and the strengths and weaknesses of religious organisations and religious leaders in conflict mediation.--Provided by publisher.